2018
DOI: 10.1186/s12958-018-0425-z
|View full text |Cite
|
Sign up to set email alerts
|

Decline in seminal quality in Indian men over the last 37 years

Abstract: BackgroundSince the first report of a decline in semen quality in 1974, there have been several reports of similar declines across populations. Despite some scattered reports of declining semen quality in the Indian sub-continent, comprehensive studies analyzing semen quality over the last few decades have not been undertaken. We undertook the present study to investigate the temporal trend in semen parameters in Indian populations over a period of 37 years (1979–2016).MethodsPublications providing semen analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 41 publications
2
42
2
3
Order By: Relevance
“…Evidence suggest that semen quality has decreased significantly over the last 40 years (Mishra et al, 2018; Sengupta, Dutta, & Krajewska‐Kulak, 2017). Oxidative stress is established as a critical factor in male infertility pathophysiology with approximately 30–80 per cent of male infertility is considered to have contribution from high ROS (Showell et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggest that semen quality has decreased significantly over the last 40 years (Mishra et al, 2018; Sengupta, Dutta, & Krajewska‐Kulak, 2017). Oxidative stress is established as a critical factor in male infertility pathophysiology with approximately 30–80 per cent of male infertility is considered to have contribution from high ROS (Showell et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that human semen quality has declined worldwide over the last several decades (Carlsen et al 1992;Mishra et al 2018). In addition to adverse lifestyle factors such as cigarette smoking, alcohol and caffeine intake, obesity, stress, and high scrotal temperature (Ilacqua et al 2018;Sadeu et al 2010;Sharpe 2000), exposure to environmental contaminants is regarded as another important contributor (Mima et al 2018;Skakkebaek et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, this is the first study on time trends in semen quality among Chinese men in Henan Province. Studies [2][3][4][5][6][7][8][23][24][25] suggest that semen quality is declining globally, however, the debate remains open due to the possible effects of ethnic and geographical differences. In contrast, several other studies have reported no significant change in semen quality [9][10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…The annualized rate of decline in the total motility was lower than that reported in America (2% per year) 23 , but it was higher than that reported in Paris (0.6% per year) 2 and Marseille (0.4% per year) 4 . The possible reasons for the discrepancy are as follows: (1) small sample size are used in the previous study 10,11 ; (2) subjects in these studies are fertile men 2,3,11 or infertile men 5,21,25 ; (3) there are differences in lifestyle habits, ethnicity, and geographical regions [2][3][4][5][6][7][8][9][10][11][22][23][24][25] ; (4) the different study periods [2][3][4][5][6][7][8][9][10][11][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%